Fit to last: Exploring the longevity of the survival processing effect. Issue 6 (June 2016) - Clark, Daniel P. A.; Bruno, Davide
Mounting evidence indicates that processing items for their survival value produces superior recall compared to a number of other well-known memory-enhancing techniques, and that this mnemonic advantage remains up to 48 hours after encoding (Raymaekers et al., 2014). However, little attention has been dedicated to the survival processing effect in location memory, which may represent a better test of adaptive memory than retrieval of verbal information. The current study aims to fill this gap by exploring the longevity of the survival processing effect with both word list (Experiment 1) and location-based (Experiment 2) stimuli. Participants rated target items using a single incidental encoding scenario, either Survival versus Pleasantness (word stimuli) or Survival versus Scavenger Hunt (location stimuli). They were then asked to complete a surprise recall task immediately after the ratings and a second recall task 96 hours later. The results demonstrated that, despite a general reduction in memory performance across time, the survival processing advantage was detected at both test times for both stimuli types. These findings provide further support for the survival processing effect and extend the observed effect duration for both word lists and location to 96 hours.